Study of Lacertilian (Lizards) diversity of District Dir (L), KPK, Pakistan: Lizard fauna - safi, Amtyaz; Ud Din Yousufzai , Sultan; Shah , Masood; Ullah , Atta; Gul , Hina; Usman Ali Hashmi , Muhammad; Karl , Hans-Volker (International Journal of Biological Research, 2024)
The current study enlightens the comprehensive picture, relative population status, and species diversity of lizard fauna in the lower Dir district of Khyber Pakhtunkhwa province, Pakistan. This study was designed to collect the data and record/investigate the population status and the diversity of lizard species from six different tehsils (Towns) in this district. We used the latest keys for identification of the collected and observed specimens. A total of 288 specimens of Lizards were examined, the collected specimens belonged to 6 families, 11 genera, and 14 species. The most abundant and observed species was H. brookii and the most abundant and observed family was Gekkonidae in this area during the current study. In this study, we have identified a new species of the genus Cyratopodion, and we will publish it after a thorough investigation in near future. The present study provides a baseline for future extensive studies on lizard habitat analysis, population dynamics, systematics, and phylogeny for incoming researchers and experts of herpetology.